2018
DOI: 10.1111/and.12973
|View full text |Cite
|
Sign up to set email alerts
|

The applied value of medical history, physical examination, colour-Doppler ultrasonography and testis scintigraphy in the differential diagnosis of acute scrotum

Abstract: Acute scrotum, especially testicular torsion, is a common surgical emergency. A delay in diagnosis or management may lead to permanent testicular ischaemic damage. Thus, it is particularly important to differentiate testicular torsion from other acute scrotum conditions as soon as possible. Our study has retrospectively investigated 358 patients with acute scrotum admitted to our hospital from the year 2007 to 2016. We have collected a thorough history and clinical data and drew the conclusion by comparing cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Moreover, our researchers observed the involvement of SULF2 in the regulation of tumor-related biological processes including angiogenesis and Wnt signaling pathways. Some researchers also reported that SULF2 was involved in various nuclear events in the cell cycle [17] as well as in the regulation of cancer development [18][19][20]. Conjointly, the above analysis suggested that miR-422a was of great potential to function as a regulator in NSCLC via regulation of SULF2.…”
Section: Mir-422a Participates Nsclc Progression By Regulating Sulf2mentioning
confidence: 90%
“…Moreover, our researchers observed the involvement of SULF2 in the regulation of tumor-related biological processes including angiogenesis and Wnt signaling pathways. Some researchers also reported that SULF2 was involved in various nuclear events in the cell cycle [17] as well as in the regulation of cancer development [18][19][20]. Conjointly, the above analysis suggested that miR-422a was of great potential to function as a regulator in NSCLC via regulation of SULF2.…”
Section: Mir-422a Participates Nsclc Progression By Regulating Sulf2mentioning
confidence: 90%
“…Hence, a prompt and accurate diagnosis is vital for TT (Bandarkar & Blask, ). TT should also be differentiated from other diseases that may cause acute scrotal pain, among which the most common one is epididymo‐orchitis (Yan et al, ). It is acknowledged that scrotal colour Doppler ultrasonography has been considered as an effective measurement in diagnosis of TT with an estimated sensitivity of 60%–85% and an estimated specificity of 70%–100% (Rebik, Wagner, & Middleton, ).…”
Section: Introductionmentioning
confidence: 99%
“…Different types of testicular tumors are treated differently, with an overall very high cure rate with proper management. Pathologists must, therefore, be familiar with important diagnostic pitfalls in testicular pathology, particularly those that result in different treatments or prognoses [ 10 ].…”
Section: Introductionmentioning
confidence: 99%